Pengelolaan Manajemen Usaha pada UMKM dan Pelatihan Pemasaran Digital di Kelurahan Cibaduyut Kidul Kecamatan Bojongloa Kidul - Retnowati, Ayu Nike; Foster, Bob; Priyana, Indarta; Purwadisastra, Dikdik (LPPM UNIBI, 2021)
The success of a country's economy is very identical to the development of Micro, Small, & Medium Enterprises (MSMEs) as a sector that absorbs high labor, MSMEs are also known as one of the real sectors that can reduce unemployment rates, which ultimately act as a driving force that plays a strategic role in urban and rural areas. The economic conditions that continue to decline as a result of the Covid 19 Pandemic make it important for the government to play a role in motivating MSME actors to mobilize their abilities to be able to adapt to the application of Digital Business. This research aimed to enhance the digital capabilities of MSME in Kecamatan Bojongloa Kidul, Bandung. By conducting a training program focused on digital marketing and financial management, the study sought to address the challenges faced by these businesses in the post-pandemic era. Training program focused on digital marketing and financial management. The results demonstrate a significant improvement in participants' understanding and application of digital tools. The findings suggest that targeted training programs can effectively empower MSME to adopt digital technologies and enhance their competitiveness in the market. Moreover, the study underscores the importance of providing ongoing support and resources to sustain the digital transformation process.